ETYMOLOGY OF ENGLISH WORDS AND NATIVE AND BORROWED ENGLISH VOCABULARY - Gʻafforov, Ibrohimjon Qobiljon oʻgʻli (INTERNATIONAL CONFERENCES, 2023)
It is no secret that learning English is becoming one of the most important tasks today. Based on this, it is interesting to study the history of the origin of English words. Based on this, we tried to find and study certain information about the language of origin of certain words and their history. We believe that this scientific article will be useful and interesting for you.